Particle migration in planar Couette-Poiseuille flows of concentrated suspensions - Kwon, Ilyoung; Jung, Hyun Wook; Hyun, Jae Chun; Chun, Myung-Suk; Chun, Byoungjin (JOURNAL RHEOLOGY AMER INST PHYSICS, 2018)
Particle migration phenomena in parallel slit channel flows of concentrated suspensions with asymmetric velocity profiles, which are governed by planar Couette-Poiseuille (C-P) flow conditions, are numerically investigated employing the diffusive flux model (DFM) via the finite volume method. The particle distributions predicted by DFM are confirmed by comparing quantitatively with those by the reported experimental results and the lattice Boltzmann method. The main factors governing the migration dynamics in the DFM, such as particle size, concentration, and flow length from an inlet of the channel, are effectively unified into a nondimensional length element. The effects of the asymmetric C-P flow fields on particle dynamics are clarified by the evolution of the concentration distribution along the nondimensional length element under a different asymmetric velocity and initial concentration conditions. From scale analysis, this asymmetric distribution is analytically interpreted by adopting a concept of the effective diffusion gap. It is substantiated that the continuum-based analysis of concentrated suspension systems reliably reflects the migration phenomenon by collisions between individual particles, focusing on the shear-induced migration process, even in the asymmetric flow conditions. (C) 2018 The Society of Rheology.
Keywords: PRESSURE-DRIVEN FLOW; NUMERICAL SIMULATIONS; CONSTITUTIVE EQUATION; BROWNIAN SUSPENSION; NORMAL STRESSES; CHANNEL; MODEL